(untitled) (Bangladesh Journal of Urology, 2020)
Objective: The objective of this article is to provide an overview of the current concepts of organ-preserving procedures for penile cancer, and describe some of their indications, results and associated complications. Methods: An extensive search of review articles of the Pubmed literature was performed to find articles discussing only organ sparing reconstructive surgery which have contributed significantly to change traditional, frequently mutilating treatments, to develop less disfiguring surgery, and to improve patients’ quality of life over the last two decades. Results: A large number of articles were included in this study in which a major contribution to the change in the treatment was thought to have occurred and was documented as beneficial. Some articles reported novel techniques of less-mutilating surgery involving different forms of glans reconstruction with the use of flaps or grafts. The issue of safe surgical margins was also addressed. Conclusion: In highly selected cases of penile carcinoma, organ preserving techniques allowing phallus preservation has reduced the negative impact on functional and cosmetic outcomes of amputation without sacrificing oncological objectives based on stage, grade, and location of the tumour. Until more prospective studies are available and strong evidence is documented, organ preservation should be offered with caution. Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.33-39